Introducing new perspectives in the use of social technologies in learning: social constructionism - Zaphiris, Panayiotis; Ioannou, Andri; Papadima-Sophocleous, Salomi; Parmaxi, Antigoni; Michailidou, Eleni (My University, 2013)
This paper reports on a qualitative study of the use of social technol-ogies, explored in the context of an intensive 650-hour Greek language course. Qualitative content analysis of instructors’ field notes, students’ and instructors’ reflections, interviews and a focus group was employed aiming at identifying the use of social technologies as a platform for constructing an online artifact. To triangulate the findings, the study also collected data by observing students’ activity with social technologies. A code scheme was developed which mani-fests the use of social technologies as a social constructionism platform identi-fying its major dimensions: exploration of ideas, construction of online artifact and evaluation of the constructed artifact. Actions within each dimension that indicate the manifestation of social constructionism are identified and dis-cussed. This study revealed results in favor of the use of social technologies as social constructing platforms suggesting a new framework for their use.
Keywords: Social technologies; Web 2.0 technologies; Social constructionism; Online artifact